Modality-specific organization in the representation of sensorimotor sequences - Boutin, Arnaud; Massen, Cristina; Heuer, Herbert (Frontiers in Psychology, 2013)
Sensorimotor representations of movement sequences are hierarchically organized. Here we test the effects of different stimulus modalities on such organizations. In the visual group, participants responded to a repeated sequence of visually presented stimuli by depressing spatially compatible keys on a response pad. In the auditory group, learners were required to respond to auditorily presented stimuli, which had no direct spatial correspondence with the response keys: the lowest pitch corresponded to the leftmost key and the highest pitch to the rightmost key. We demonstrate that hierarchically and auto-organized sensorimotor representations are developed through practice, which are specific both to individuals and stimulus modalities. These findings highlight the dynamic and sensory-specific modulation of chunk processing during sensorimotor learning – sensorimotor chunking – and provide evidence that modality-specific mechanisms underlie the hierarchical organization of sequence representations.